Temporal-Spatial Analysis of Traffic Congestion Based on Modified CTM. (19th October 2015) - Chu, Chenglong; Xie, Na; Chen, Xiqun; Wu, Yuxin; Sun, Xiaoxiao
Abstract : A modified cell transmission model (CTM) is proposed to depict the temporal-spatial evolution of traffic congestion on urban freeways. Specifically, drivers' adaptive behaviors and the corresponding influence on traffic flows are emphasized. Two piecewise linear regression models are proposed to describe the relationship of flow and density (occupancy). Several types of cellular connections are designed to depict urban rapid roads with on/off-ramps and junctions. Based on the data collected on freeway of Queen Elizabeth, Ontario, Canada, we show that the new model provides a relatively higher accuracy of temporal-spatial evolution of traffic congestions.